2014
DOI: 10.1186/1471-2334-14-431
|View full text |Cite
|
Sign up to set email alerts
|

Decline in severe diarrhea hospitalizations after the introduction of rotavirus vaccination in Ghana: a prevalence study

Abstract: BackgroundAlmost all diarrhea deaths in young children occur in developing countries. Immunization against rotavirus, the leading cause of childhood severe dehydrating acute diarrhea may reduce the burden of severe diarrhea in developing countries. Ghana introduced rotavirus and pneumococcal vaccination in the national expanded program on immunization in May 2012.MethodsReview of all-cause diarrheal hospitalization data for children aged 59 months and younger at 2 pediatric referral hospitals in southern Ghana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 18 publications
4
33
0
Order By: Relevance
“…Studies showed rotavirus as the most common cause of vaccine-preventable diarrheal disease during dry seasons [ 1 , 23 ]. Childhood diarrhea among children who received rotavirus vaccine was also less compared to children who did not receive rotavirus vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed rotavirus as the most common cause of vaccine-preventable diarrheal disease during dry seasons [ 1 , 23 ]. Childhood diarrhea among children who received rotavirus vaccine was also less compared to children who did not receive rotavirus vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic studies indicated diarrheal diseases, which are widespread in areas with water scarcity, unsafe drinking water supply, poor hygiene, and lack of sanitation which are poorly accessed [ 21 , 22 ]. However, in rotavirus-vaccinated children, occurrence of childhood diarrhea decreased significantly [ 23 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination can also reduce emissions, although ignored in our study. Rotavirus vaccination offers reductions in mortality and morbidity in some developing countries, despite efficacy challenges from the wide variability of circulating strains (Enweronu-Laryea et al, 2014;Fischer Walker and Black, 2011). Finally, we highlight that the models aim to estimate annual average daily total emissions.…”
Section: Discussionmentioning
confidence: 99%
“…We developed future management scenarios for RV and EC emissions of the GloWPa‐H1 and KlaWPa‐H1 models from three actor‐based strategies: (i) the Ministry of Water and Environment sector development plan for the financial year 2019–2020 (MWE, 2016, 2017) to increase onsite sanitation coverage and reach 100% coverage in small towns and rural growth areas, and the Ministry of Health's Uganda Sanitation Fund Program to improve access to basic onsite sanitation, promote household hygiene, and end open defecation (Global Sanitation Fund, 2017); (ii) NWSC's 5‐yr plan to improve sewer coverage from 7 to 30% in their districts of operation between 2016 and 2021 (NWSC, 2016) and comply with treatment effluent discharge standards; and (iii) the UN 2015 SDG resolution 6.3 on halving untreated wastewater by 2030 (United Nations, 2015). Table 2 shows baseline conditions (BS) in 2015 and scenario descriptions for 2030: S1 is “Business as Usual,” S2 is “Industrious,” and S3 is “Low Emissions.” Changes in population, sanitation, and wastewater treatment are developed based on the actor‐based strategies.…”
Section: Methodsmentioning
confidence: 99%
“…Vaccine coverage has increased substantially from 42-56% in 2012 to above 90% in 2016, [15,16]. Early vaccine evaluations of RV1 have shown moderate and varied reduction in both rotavirus and all-cause diarrhea hospitalizations among <5-year-olds [15][16][17]. Additional benefits may be derived from rotavirus vaccination if strategies are identified to improve the vaccine effectiveness.…”
Section: Introductionmentioning
confidence: 99%